Urinary tract infection in children: Assessment of antibiotic susceptibility profile - Teixeira, Susana Cláudia (2023)
Introduction: Urinary tract infections are among the most common bacterial infections in children. Knowing the local prevalence of uropathogens and their antibiotic susceptibility patterns is essential for appropriate empirical antimicrobial therapy. The aim of this study was to evaluate the etiological bacterial organisms of community-acquired urinary tract infections in pediatric age and their antibiotic susceptibility profile in the area of influence of a secondary hospital in northern Portugal. Material and Methods: Retrospective study of all urine cultures from the Pediatric Emergency Department of Centro Hospitalar de Trás-os-Montes e Alto Douro, Vila Real, Portugal, between July 2017 and June 2020. Etiology and antimicrobial susceptibility data were analyzed by gender and age group. Results: Of 2225 urine cultures, 541 were positive for bacterial infection. Urinary tract infections were more common in females (72.8%), except in children under one year of age. Escherichia coli (76.9%) and Proteus mirabilis (15.1%) were the most frequently isolated organisms. Both uropathogens had higher susceptibility rates to cefuroxime than to amoxicillin-clavulanic acid. E. coli isolates from males between one and three years of age had a susceptibility rate of 38.1% to amoxicillin-clavulanic acid. In females over 16 years of age, all E. coli isolates were susceptible to fosfomycin and nitrofurantoin. Discussion: E. coli was the most common pathogen isolated in both genders. In the authors’ perspective, cefuroxime should be considered as a first-line empirical treatment, especially in males between one and three years of age. Conclusion: Regular monitoring of the local antibiotic susceptibility profile should be performed to optimize empirical antibiotic therapy. Not only age but also gender should be taken into account.